Re-organise: Game-Based Learning of Circular Business Model Innovation - Lange, Kasper P. H.; Korevaar, Gijsbert; Oskam, Inge F.; Herder, Paulien M. (Frontiers in Sustainability, 2022)
This article demonstrates how and to what extent game-based learning can improve teaching circular business model innovation (CBMI), which is the complex, dynamic process of designing business models for the circular economy. We conducted an experiment with two groups of students using a game education package called Re-Organise. All students filled out a circular business model canvas and a learning reflection after studying a reader and a game role description. The experiment group updated both the canvas and the reflection in an interactive tutorial after gameplay. The control group submitted their work only after the interactive tutorial. The results were analysed using text-mining and qualitative methods, e.g., word co-occurrence and sentiment polarity. The game group created richer business models (using more waste processing technologies), and reflections with stronger sentiments towards the learning experience. Thus, board games can be effective tools to teach the intricacies of CBMI in a realistic manner.